PENGAMBILAN KEPUTUSAN DALAM MEMILIH FOTOGRAFER WEDDING - Buana, Tommy Pradhipta; Sulandari, Santi (Psikologi UHAMKA, 2021)
Marriage is a sacred moment, where men and women unite in bonds according to laws, norms, and religions. A lot of people nowadays has a big desire to capture this moment into a memorable photo. Many wedding photo service providers undoubtedly make consumers feel confused about their choice of photo vendors. This research has fundamental question about